2021
DOI: 10.1038/s41598-020-78062-2
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting methylation predicts hippocampal volumes and hyperintensities and the change with age in later life

Abstract: Epigenetic imprinting is important for neurogenesis and brain function. Hippocampal volumes and brain hyperintensities in late life have been associated with early life circumstances. Epigenetic imprinting may underpin these associations. Methylation was measured at 982 sites in 13 imprinted locations in blood samples from a longitudinal cohort by bisulphite amplicon sequencing. Hippocampal volumes and hyperintensities were determined at age 64y and 72y using MRI. Hyperintensities were determined in white matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Loss of function of peg3 in mouse placenta leads to low birth weight in pups (Creeth & John, 2020). In the ABC1936 cohort, it could be shown that PEG3 methylation predicted hyperintensities in hippocampal gray and white matter in the participants at age 64 and 72 (Lorgen‐Ritchie et al, 2021). As low birth weight is one of the best validated developmental risk factor for ADHD, in future studies, the birth history will be reported and it might be of interest to investigate the PEG3 methylation level as well.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function of peg3 in mouse placenta leads to low birth weight in pups (Creeth & John, 2020). In the ABC1936 cohort, it could be shown that PEG3 methylation predicted hyperintensities in hippocampal gray and white matter in the participants at age 64 and 72 (Lorgen‐Ritchie et al, 2021). As low birth weight is one of the best validated developmental risk factor for ADHD, in future studies, the birth history will be reported and it might be of interest to investigate the PEG3 methylation level as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, oxo8dG and 5hmC in CGIs can induce DNA hypomethylation by inhibiting DNA methylation or activating the DNA demethylation processes 193 . Additionally, there is evidence showing that H19/IGF2 methylation states are potentially relevant to hippocampal structure and function across the life course 595 , 596 . Taken together, the decline in CTCF may cooperate with the gained methylation on ICR at the initial stage of AD to induce LOI of IGF2, which then may cause cascade events resulting in LOI of H19.…”
Section: Loss Of Proteostasismentioning
confidence: 99%
“…Genetics and environment can both have an impact on imprints. Variation in the sequence underlying the assessed epigenetic regions may have an impact on epigenetic states for genetic effects [17]. Imprinted genes have an unusual function in germ cells, in reprogramming events.…”
Section: Methylation-specific Real-time Pcr For the Identification Of...mentioning
confidence: 99%